Upaya Meningkatkan Hasil Belajar Dengan Model Pembelajaran Demontrasi Berbantuan Lembarkerja Siswa (LKS) Di Kelas VII SMP Negeri 9 Padangsidimpuan Tahun Ajaran 2021/2022 - Makrup Hasbi; Adek Nilasari Harahap; Haritsah Hammamah Harahap (JURNAL CERMATIKA, 2023)
This research method used is classroom action research using two cycles carried out in the first semester with Set material.The population in this study were VII grade students of SMP Negeri 9 Padangsidempuan as many as 30 people. The class that was used as the sample was class VII-2 of SMP Negeri 9 Padangsidimpuan with 30 students. As the sample is class VII-2 SMP Negeri 9 Padangsidimpuan which will use the demonstration method aided by the set material. will use the demonstration method assisted by student worksheets (lks) in learning. learning. The ability of student learning outcomes in learning mathematics inclass VII-2 SMP Negeri 9 Padangsidempuan on set material increased by 62.4% with the category "sufficient" in cycle I, then increased to 91% with the category "good" in cycle II. with the category "good" in cycle II. Increased student learning activities on set material in the cycle with a percentage result of 75.08% and in cycle II the results increased to 87.27%. For teacher ability in cycle I obtained an average activity score of 3.40 (good) and in cycle IIobtained an average activity score of 3.68 (very good).